Giving MP-ASI too early to babies in Pagaran Tonga Village, Panyabungan District, Mandailing Natal Regency in 2023 - Helmi Wardah Nasution; Ferika Desi; Khoirunnisaa Batubara; Dewi Sri Rahayu Tinendung (IJCS: International Journal of Community Service, 2023)
Early complementary foods (MP-ASI) are additional foods given to infants at the age of less than 6 months in addition to breast milk. Child health organizations in America recommend complementary feeding (MP-ASI) at the age of 6 months for babies who get exclusive breastfeeding, and at the age of 4-6 months for babies who get formula milk. Community service activities are carried out at the village office. The counseling will be held for 1 (one) day, namely on January 26, 2023, at 10.00 WIB until it is completed in Pagaran Tonga Village, Panyabungan District, Mandailing Natal Regency. The material was delivered by providing counseling on Giving MP-ASI Too Early to Infants, then continued with the provision of snacks with the involvement of 5 students of the Midwifery DIII study program, Madina Husada. The final result that can be seen from this activity is that most participants understand about giving MP-ASI to babies. Participants also follow the committee's direction. Counseling activities on giving MP-ASI too early to infants in Pagaran Tonga Village, Panyabungan District, have been successfully carried out.